2012
DOI: 10.5432/ijshs.201208
|View full text |Cite
|
Sign up to set email alerts
|

Coach-athlete Relationships: A Qualitative Study of Professional Sport Teams in Australia

Abstract: This paper examines perceptions of eŠective coaching and coach-athlete relationships within professional team sports in Australia. Theˆndings are based on interviews with six male professional coaches and 25 players from cricket, rugby league, and rugby union. Qualitative data analysis reveals that relationships within professional sport settings are based on mutual respect, trust and honesty. The results also indicate that professional coaches and players describe two diŠerent types of coach-athlete relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 3 publications
1
11
0
3
Order By: Relevance
“…31 Feedback about coaching performance, particularly from a knowledgeable and experienced individual is an essential element of the process of developing expertise and is critical particularly in facilitating coaches’ transitions to higher levels of accreditation. 54 However, both Cushion et al. 55 and Gearity 56 have suggested that athletes prefer coaches who display coaching behaviours that suit their learning style.…”
Section: Resultsmentioning
confidence: 99%
“…31 Feedback about coaching performance, particularly from a knowledgeable and experienced individual is an essential element of the process of developing expertise and is critical particularly in facilitating coaches’ transitions to higher levels of accreditation. 54 However, both Cushion et al. 55 and Gearity 56 have suggested that athletes prefer coaches who display coaching behaviours that suit their learning style.…”
Section: Resultsmentioning
confidence: 99%
“…Study has shown that the most effective leadership style is the democratic one in which the leader-supervisor distributes as much power to his subordinates as (Schmuck, 1968), while unwanted leadership is considered the authoritarian (Surujlal, & Dhurup, 2012). In addition, three attributes of an effective leader were recorded: development of interpersonal relationships, division of competences and decision-making (Bennie & O'Connor, 2012), with socially supportive leadership style to stimulate team morale (Bray, Millen, Eidsness, & Leuzinger, 2005;Hampson & Jowett, 2014) and reinforce their desire to participate in physical activities outside of work (Chatzisarantis & Hagger, 2009 (Monemi & Moghaddam, 2013), while the authoritarian style is associated positively with anxiety and the use of verbal aggressive behaviour by the leader (Bekiari, 2014). Conclusively, the supervisors with their behaviour and the way that they perform their tasks affect the job satisfaction of the subordinates, promoting the production and implementation of innovative ideas within the enterprise (DeJong & DenHartog, 2007).…”
Section: Leadership Stylementioning
confidence: 99%
“…Furthermore, due to the potential reciprocal effect on need fulfillment between different contexts it seems valuable for coaches to demonstrate a genuine care for athletes' lives outside of the sport environment. More specifically, it is difficult for athletes to trust coaches who do not show an interest in them on a personal level or can have a conversation about something nonsport related (Bennie & O'Connor, 2012). The results of this study also suggest that coaches of interactive teams may want to consider ways that help them nurture individual relationships with each member of their team.…”
Section: Practical Implicationsmentioning
confidence: 87%